AN ANALYTICAL STUDY OF PACKAGING INDUSTRIES WITH REFERENCE TO CHAKAN MIDC AREA (International Journal of Engineering Sciences & Management Research, 2016)
Packaging is the science, art and technology of enclosing or protecting products for distribution, storage, sale, and use. Packaging also refers to the process of design, evaluation, and production of packages. Packaging can be described as a coordinated system of preparing goods for transport, warehousing, logistics, sale, and end use. Packaging contains, protects, preserves, transports, informs, and sells. In many countries it is fully integrated into government, business, institutional, industrial, and personal use.